Characteristics of VOCs and their Potentials for O3 and SOA Formation in a Medium-sized City in Eastern China - Peilin Chen; Xinye Zhao; Ou Wang; Min Shao; Xinxin Xiao; Shanshan Wang; Qin’geng Wang (Aerosol and Air Quality Research)
Abstract To understand the characteristics and environmental effects of volatile organic compounds (VOCs) in a typical medium-sized city in China, manual measurements including 56 species of the nonmethane hydrocarbons (NMHCs) were taken at three urban and suburban sites in Huai’an from April to September 2019, and automatic measurements including 106 species of VOCs were taken at the urban center in May and August 2019. Spatial and temporal characteristics of the VOC concentrations were analyzed. Positive matrix factorization (PMF) model was applied to apportion VOC sources. Ozone (O3) formation potentials (OFPs) and secondary organic aerosol (SOA) formation potentials (SOAFPs) were calculated. The results show that the mean VOC concentration was much lower in the urban center than in the suburbs. Generally, proportions of both alkenes and aromatic hydrocarbons were higher and proportion of alkanes was lower in Huai’an than that in big cities, indicating emissions from solvent usage and industrial process play a more important role in the medium-sized city. The results of source apportionment show that solvent usage and industrial process together contributed 53%, and vehicle emission contributed 27% to the ambient VOCs. The dependence of VOC concentrations on temperature indicates that a considerable part of VOCs may come from fugitive emissions. The two-peak pattern of diurnal variation suggests near-surface emissions contributed a lot to the VOCs. Aromatic hydrocarbons were identified as the key component to the formation of O3 and SOA. Furthermore, biogenic emission could contribute greatly (> 20%) to the ambient VOCs during daytime in summer, which may have significant effects on O3 formation. Aromatic hydrocarbons were identified as the key component to the formation of O3 and SOA, which should be given more attention in developing air pollution control strategies.